APKASS Consensus Statement on Chronic Syndesmosis Injury, Part 1: Clinical Manifestation, Radiologic Examination, Diagnosis Criteria, Classification, and Nonoperative Treatment. Issue 6 (18th June 2021) - Jiao, Chen; Gui, Jianchao; Kurokawa, Hiroaki; Tanaka, Yasuhito; Yung, Patrick; Han, Seung Hwan; Angthong, Chayanin; Song, Yujie; Hua, Yinghui; Li, Hongyun; Shi, Zhongmin; Li, Qi; et al.
Background: Clinical manifestation, radiologic examination, diagnostic criteria, classification, and nonoperative treatment strategies regarding chronic syndesmosis injury remain unclear. Purpose: An international group of experts representing the fields of sports injuries in the foot and ankle area were invited to collaboratively advance toward consensus opinions based on the best available evidence regarding chronic syndesmosis injuries. All were members of the Asia-Pacific Knee, Arthroscopy and Sports Medicine Society (APKASS). Study Design: Consensus statement. Methods: From November to December 2020, a total of 111 international experts on sports medicine or ankle surgery participated in a 2-stage Delphi process that included an anonymous online survey and an online meeting. A total of 13 items with 38 statements were drafted by 13 core authors. Of these, 4 items with 15 clinical questions and statements were related to the clinical manifestation, radiologic examination, diagnostic criteria, classification, and nonoperative treatment strategies for chronic syndesmosis injury and are presented here. Each statement was individually presented and discussed, followed by a general vote. The strength of consensus was characterized as follows: consensus, 51% to 74%; strong consensus, 75% to 99%; unanimous, 100%. Results: Of the 15 questions and statements, 5 reached unanimous support and 10 achieved strong consensus. Conclusion: This APKASS consensus statement, developed by international experts in the field, will assist surgeons and physical therapists with diagnosis, classification, and nonoperative treatment strategies for chronic syndesmosis injury.